MEMAHAMI INGATAN KULTURAL YAHUDI DALAM KONFLIK ISRAEL-PALESTINA - Leonard C. Epafras (Universitas Gadjah Mada, 2013)
This article is an assessment to the role of the Jewish cultural memory in the Israeli-Palestinian conflict.Cultural memory in this regard is a social or collective memory that links to the fateful moment(s) inthe past. These past experiences shape the ones identities, way of life, self-image and perception, andthe attitude toward the others. Jewish cultural memory is supplied by religious narratives, diasporaexperiences, the emergence of Zionism, Holocaust/Shoah, and the rebirth of Masada historical moment.Those memories have a strong influence toward Israeli government in dealing with the conflict with theArabs, especially with Palestinians.